Attracting Customers Interest through Celebrity Endorses for Marketplace - Putra, Defin Shahrial; Yulianti, Farida; Abdurrahim, Abdurrahim (JDM (Jurnal Dinamika Manajemen), 2020)
This study aims to determine the tendency of celebrity endorse mediated by brand awareness impact to attract buying interest from the public. This is because celebrities are people who are well known to the public and have there are charm. So that with the support of celebrities will have an impact on the sale of their products. Some marketplaces use celebrities as brand ambassadors to attract buyers, besides it will give celebrity brands that are constantly remembered by customers. In this study because the population is unknown, the sampling technique uses purposive sampling as many as 310 respondents. The analysis technique used is Structural Equation Modeling (SEM). The results show that brand awareness mediates the influence of celebrities on customer interest when a celebrity carries advertisements will give the impression to customers that the celebrity has a good reputation and attractiveness will have a good impact. Besides the marketplace in choosing a celebrity will look for those who can deliver advertisements with professionals. The implication of this research is the need for celebrity support related to the importance of attracting people’s purchasing power to the marketplace, in addition to a well-known combination of a good reputation and attractive appearance has added value that will provide reminders to customers.